Case fatality rate and length of hospital stay among patients with typhoid intestinal perforation in developing countries: a systematic literature review. - Vittal Mogasale; Sachin N Desai; Vijayalaxmi V Mogasale; Jin Kyung Park; R Leon Ochiai; Thomas F Wierzba (PLoS ONE)
Background Typhoid fever remains a major health problem in the developing world. Intestinal perforation is a lethal complication and continues to occur in impoverished areas despite advances in preventive and therapeutic strategies. Objectives To estimate the case fatality rate (CFR) and length of hospital stay among patients with typhoid intestinal perforation in developing countries. Data sources Peer-reviewed publications listed in PubMed and Google Scholar. Study eligibility The publications containing data on CFR or length of hospitalization for typhoid fever from low, lower middle and upper middle income countries based on World Bank classification. Limits are English language, human research and publication date from 1st January 1991 to 31st December 2011. Participants Subjects with reported typhoid intestinal perforation. Interventions None, standard practice as reported in the publication. Study appraisal and synthesis methods Systematic literature review followed by meta-analysis after regional classification on primary data. Descriptive methods were applied on secondary data. Results From 42 published reports, a total of 4,626 hospitalized typhoid intestinal perforation cases and 706 deaths were recorded (CFR = 15·4%; 95% CI; 13·0%-17·8%) with a significant regional differences. The overall mean length of hospitalization for intestinal perforation from 23 studies was 18.4 days (N = 2,542; 95% CI; 15.6-21.1). Limitations Most typhoid intestinal perforation studies featured in this review were from a limited number of countries. Conclusions The CFR estimated in this review is a substantial reduction from the 39.6% reported from a literature review for years 1960 to 1990. Aggressive resuscitation, appropriate antimicrobial coverage, and prompt surgical intervention may have contributed to decrease mortality. Implications The quantification of intestinal perforation outcomes and its regional disparities as presented here is valuable in prioritizing and targeting typhoid-preventive interventions to the most affected areas.